2019
DOI: 10.1002/sono.12189
|View full text |Cite
|
Sign up to set email alerts
|

Sonographer credentialing in extended focussed assessment by sonography in trauma (eFAST)

Abstract: Introduction: Sonographers of a large, metropolitan health service were trained and credentialed in extended focussed assessment by sonography in trauma in preparation for a potential mass casualty incident. Given the prior ultrasound experience of this cohort, the suitability of an abbreviated credentialing pathway based upon that required for emergency physicians was evaluated. Method:A training and credentialing process to teach extended focussed assessment by sonography in trauma was planned for sonographe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It contradicts previous research. Such studies showed that clinical radiographers’ competence in using CT and USG scans to diagnose medical conditions grew dramatically with education ( 19 , 20 ). Our study only used CT or USG scans to diagnose acute appendicitis, which may explain the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…It contradicts previous research. Such studies showed that clinical radiographers’ competence in using CT and USG scans to diagnose medical conditions grew dramatically with education ( 19 , 20 ). Our study only used CT or USG scans to diagnose acute appendicitis, which may explain the discrepancies.…”
Section: Discussionmentioning
confidence: 99%